Acute appendicitis and situs viscerum inversus: radiological and surgical approach—a systematic review - Giuseppe Di Buono; Salvatore Buscemi; Massimo Galia; Elisa Maienza; Giuseppe Amato; Giulia Bonventre; Roberta Vella; Marta Saverino; Emanuele Grassedonio; Giorgio Romano; Antonino Agrusa (European Journal of Medical Research, 2023)
Abstract Introduction Acute appendicitis is one of the most frequent intra-abdominal diseases requiring emergency surgical consult and treatment. The diagnosis of this condition is based on clinical features and radiologic findings. One-third of patients with acute appendicitis present unusual symptoms. There are several circumstances that may cause misdiagnosis and unclear prognostic prediction. Among these, situs viscerum inversus totalis and midgut malrotation can be challenging scenarios, leading to a delay in treatment, especially when these conditions are unknown. We decided to carry on a systematic review of published cases of acute appendicitis in the context of anatomical anomalies. Methods We used the MESH terms “appendicitis” AND “situs inversus” AND/OR “gut malrotation” to search for titles and abstracts. Inclusion criteria were patients with clinical and/or radiological diagnosis of acute appendicitis, with conservative or surgical management and with preoperative/intraoperative findings of situs viscerum inversus or gut malrotation. Additionally, previous reviews were examined. Exclusion criteria of the studies were insufficient patient clinical and demographic data. Results We included in this review 70 articles concerning 73 cases of acute appendicitis with anatomical anomaly. Patients were aged from 8 to 86 years (median: 27.0 years). 50 were male and 23 were female. 46 patients (63%) had situs viscerum inversus, 24 (33%) had midgut malrotation, 2 (2.7%) had Kartagener’s syndrome, one of them (1.4%) had an undetermined anomaly In 61 patients the anatomical anomaly was unknown previously (83.6%), while 16,4% already were aware of their condition. Conclusion Acute appendicitis can occur in association of rare anatomical anomalies and in these cases diagnosis can be challenging. Situs viscerum inversus and midgut malrotation should always be considered in the differential diagnosis of a patient with left lower quadrant pain, especially in younger population. Besides clinical features, it is fundamental to implement the diagnostic progress with radiological examination. Laparoscopic approach is useful to identify and treat acute surgical emergency and it is also a diagnostic tool and can be tailored in order to offer the best exposition of the operatory field for each single case.